2015
DOI: 10.1093/geront/gnv030
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Memory Change on Daily Life in Normal Aging and Mild Cognitive Impairment

Abstract: There are similarities and important differences in the impact of mild memory change on the everyday lives of older adults with age-normal memory changes and those with aMCI. Findings underscore the need for clinical interventions that aim to minimize the emotional impact of memory changes and that increase leisure and social activity in individuals with aMCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 28 publications
2
85
0
1
Order By: Relevance
“…Avoidant coping was also a key observation of the qualitative study of 14 individuals with amnestic MCI reported by Parikh et al 30 These individuals reported withdrawing from the social activities they previously enjoyed to avoid embarrassment and frustration when their memory fails them in these settings. Social exclusion was also reported, such as being interrupted when they hesitate in conversations, and feeling that their friends no longer share information with them in the way they had previously.…”
Section: Phenomenology Of MCImentioning
confidence: 93%
“…Avoidant coping was also a key observation of the qualitative study of 14 individuals with amnestic MCI reported by Parikh et al 30 These individuals reported withdrawing from the social activities they previously enjoyed to avoid embarrassment and frustration when their memory fails them in these settings. Social exclusion was also reported, such as being interrupted when they hesitate in conversations, and feeling that their friends no longer share information with them in the way they had previously.…”
Section: Phenomenology Of MCImentioning
confidence: 93%
“…Changes in cognitive ability affect the lives of elderly people. However, the extent of this impact has been reported to be more significant and more negative in those with mild cognitive impairment (MCI) that is not serious enough to interfere with everyday activities [1]. Moreover, individuals with MCI are at an increased risk of developing Alzheimer's [2] or other forms of dementia [3].…”
Section: Introductionmentioning
confidence: 99%
“…This is a particular problem for older adults with amnestic mild cognitive impairment (aMCI), which is characterized by explicit memory deficits greater than expected according to one's age (Albert et al, 2011;Petersen, 2004), and is a likely precursor to dementia due to Alzheimer's disease (AD). As explicit memory begins to decline, people with aMCI are vulnerable to withdrawal from social and leisure activities in part because of potential embarrassment around forgetting the names of friends and acquaintances (Parikh, Troyer, Maione, & Murphy, 2016).…”
Section: Introductionmentioning
confidence: 99%